2020
DOI: 10.1080/10942912.2020.1720712
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nonvolatile taste components in 18 strong fragrance spices

Abstract: In order to investigate the taste compounds of 18 strong fragrance spices, high performance liquid chromatography was used to determine the content of free amino acids, nucleotides and organic acids. Cluster analysis was used to classify on the basis of similar data. The results showed that the content of free amino acid in tarragon was the highest, 44.97 g/kg, followed thyme, 11.88 g/kg. The contents of organic acids in 3 spice samples were significantly higher compared with others, including thyme (54.67 g/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
2
27
0
1
Order By: Relevance
“…Mori et al [35] reported that 5′-IMP and 5′-GMP were the main 5′-nucleotides. These findings were similar to those reported by Duan et al [9] Moreover, 5′-nucleotides could reduce the generation of unpleasant flavor during food processing [36]. Therefore, the amount of salt could be reduced by adding 5′-IMP and 5′-GMP or a mixture of them in food products, which will reduce the risk of diseases caused by excessive salt intake [37].…”
Section: Analysis Of 5′-nucleotidessupporting
confidence: 88%
See 3 more Smart Citations
“…Mori et al [35] reported that 5′-IMP and 5′-GMP were the main 5′-nucleotides. These findings were similar to those reported by Duan et al [9] Moreover, 5′-nucleotides could reduce the generation of unpleasant flavor during food processing [36]. Therefore, the amount of salt could be reduced by adding 5′-IMP and 5′-GMP or a mixture of them in food products, which will reduce the risk of diseases caused by excessive salt intake [37].…”
Section: Analysis Of 5′-nucleotidessupporting
confidence: 88%
“…Horseradish has highest content of total free amino acids (46.67 g/kg) because of its higher total bitter amino acids content (40.26 g/kg), especially with the content of Arg (24.84 g/kg). The bitter free amino acids are rich in pungent spices, which is similar to strong fragrance spices [9] and elegant spices [10]. The proportion of umami free amino acids in 3 spices were more than 50%, including white mustard (58.7%), black mustard (67.6%), and peppermint (75.1%).…”
Section: Analysis Of Free Amino Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…is information confirmed the abundance of pharmacological properties of LPH. According to the Chinese natural spices classification standard (GB/T 21725-2017), LPH with a strong aroma is characterized as one of the 20 pungent type spices [20,21]. Based on its unique characteristics of citrus, sweet lemon, camphor wood, and green aroma, LPH is also a vital fragrance applied to many southwestern Chinese dishes, such as cooking beef or lamb, chili sauce, and pickled vegetables, especially the traditional Zhijiang Blood Duck (Huaihua, Hunan province) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%